P-OGC34 Pandemic paradigms: Early outcomes of radical chemoradiotherapy for patients with operable oesophageal and oesophago-gastric junctional adenocarcinoma. (16th December 2021) - Rupasinghe, Sukitha Namal; Ninkovic-Hall, George; Mckinney, Rachel; Howes, Nathan; Rao, Rohith; Gunasekera, Rohan; Grocock, Christopher; Hartley, Mark; Kaul, Anil; Javed, Muhammad Shafiq; Stephens, Nathan
Abstract: Background: The peak waves of the COVID pandemic necessitated a paradigm shift in surgical management of patients with oesophageal adenocarcinoma due to both pressure on services and high mortality rates for those with COVID undergoing surgery. The Association of Upper GI Surgeons (AUGIS) guidance on treating Upper gastrointestinal cancers in the COVID era made suggestions to treat operable adenocarcinomas using definitive/consolidation chemoradiation (DCRT) over standard neo-adjuvant chemotherapy (NAC) and our unit altered practice accordingly for a cohort of patients. For affected patients we monitored and audited clinical outcomes and the initial results from this are presented here. Methods: Patients with oesophageal or oesophago-gastric junctional (O/OGJ) adenocarcinoma with potentially curative disease where initial management was altered from a treatment path which would have included surgery (with or without neoadjuvant therapy) to DCRT discussed at our regional multidisciplinary team (MDT) meeting between 1st February-1st June 2020 were included. Patient demographics, investigations, treatment given and clinical outcomes were prospectively recorded.   Results: 31 Patients with operable adenocarcinoma of O/OGJ had treatment altered to DCRT (mean age 65.4, [range 43 – 79]), 28 (90%) Male. 1 patient deteriorated prior to starting, leaving 30 who completed DCRT.  Of these 4 patients had already had NAC prior to DCRT.  Follow up was for a median of 8 (range 4-8) months following start of treatment. Post- vs pre-treatment FDG-PET imaging demonstrated a significant reduction in the mean maximum standardized uptake value (SUVmax) (p = 0.003, Sign test), in all but 3 patients.  11 patients had DCRT alone, (all alive at the time of data collection), of whom 3 patients had no sign of tumour. 19 (56%) patients proceeded to salvage oesophagectomy at a median of 15(range 10-25) weeks after completion of DCRT. 42% of these patients had a complete pathological response to treatment. There was a 5% perioperative mortality rate for this group and 1 patient was found to be unresectable on the day of surgery. At the time the data was reviewed overall survival of the entire cohort was 91%, 56% of whom had no sign of residual or recurrent disease. Conclusions: A disease free survival of 56% compares poorly with the literature at the 3-month interval. The long-term follow-up of these patients will only be apparent in the coming months and years. This data does not support the use of this modality in the future and alternate treatment plans should be devised for future pandemics.